2016
DOI: 10.3390/nano6030043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saturation Pressure Difference on Metal–Silicide Nanopowder Formation in Thermal Plasma Fabrication

Abstract: A computational investigation using a unique model and a solution algorithm was conducted, changing only the saturation pressure of one material artificially during nanopowder formation in thermal plasma fabrication, to highlight the effects of the saturation pressure difference between a metal and silicon. The model can not only express any profile of particle size–composition distribution for a metal–silicide nanopowder even with widely ranging sizes from sub-nanometers to a few hundred nanometers, but it ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Although its computational costs are low, its mathematical formulation is more complex; nevertheless, it still requires an assumption of a lognormal size distribution. Type D can express a size distribution with any shape during collective nanoparticles’ growth through simultaneous processes of nucleation, condensation, and coagulation [ 37 , 48 , 49 , 53 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Its mathematical description is more complex; furthermore, its computational costs are higher because the equations as many as the nodes discretizing the size distribution.…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…Although its computational costs are low, its mathematical formulation is more complex; nevertheless, it still requires an assumption of a lognormal size distribution. Type D can express a size distribution with any shape during collective nanoparticles’ growth through simultaneous processes of nucleation, condensation, and coagulation [ 37 , 48 , 49 , 53 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Its mathematical description is more complex; furthermore, its computational costs are higher because the equations as many as the nodes discretizing the size distribution.…”
Section: Numerical Model Descriptionmentioning
confidence: 99%
“…T from the kinetic theory [37]. This growth-transport model obtains the spatial distributions of the number density and mean diameter of nanoparticles with a lower computational cost than those of other models [12][13][14][15][16][17][19][20][21][22][23][24][25][26][27].…”
Section: Model Descriptionmentioning
confidence: 99%
“…Theoretical modeling and numerical studies are effective approaches, as demonstrated by other thermal plasma systems with nanopowder formation [12][13][14][15][16][17][18][19][20][21]. For an arc plasma process, Tashiro et al [22] conducted a numerical calculation based on an oversimplification that small particles do not collide and that only large particles collide and form agglomerates in a two-dimensional space.…”
Section: Introductionmentioning
confidence: 99%
“…They succeed in determining several parameters effects’, such as the droplet size, injection angle, and nanoparticles velocity, on the growth process. On other hand, Shigeta and Watanabe theoretically examine the size distribution and the growth process dependency on the saturation pressure, by simulating metal silicide nanoparticles using a thermal plasma [ 28 ]. Later, Shigeta addresses the turbulence effect on thermal plasma flow as it is a major contributor in the generation of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%